2012
DOI: 10.1038/oby.2011.351
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Factors Contributing to Sibling Correlations in BMI: A Study Using the Panel Study of Income Dynamics

Abstract: Understanding the mechanisms contributing to correlated BMI outcomes in a social network such as siblings will help policy makers reduce the burden of disease associated with obesity. There are two potential mechanisms explaining correlated BMI outcomes in a biologically related social network: (i) time constant factors such as genetic heritability and habits formed during childhood and (ii) factors that change over time some of which are dependent on the frequency of interactions between the social network, f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 29 publications
0
27
1
1
Order By: Relevance
“…Previous studies have shown the greatest absolute BMI increase was within the already heaviest population [33], and only a moderate amount of SBP and DBP is accounted for by genetic factors [34], indicating the unignorable large impact of shared environment. Recently, Brown et al further added that, based on a US sibling cohort, sharing the same household could facilitate the social network influence on correlations in BMI [35]. Meanwhile, in our study, despite relatively low BMI, SBP and DBP levels in rural areas and low income families, statistically significant ICCs of overweight/obesity (BMI ≥ 25 kg/m 2 ) were only shown in rural areas, and those of high BP (SBP ≥ 120 mmHg or DBP ≥ 80 mmHg) were presented in low-income families and in regions of all modernization levels.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown the greatest absolute BMI increase was within the already heaviest population [33], and only a moderate amount of SBP and DBP is accounted for by genetic factors [34], indicating the unignorable large impact of shared environment. Recently, Brown et al further added that, based on a US sibling cohort, sharing the same household could facilitate the social network influence on correlations in BMI [35]. Meanwhile, in our study, despite relatively low BMI, SBP and DBP levels in rural areas and low income families, statistically significant ICCs of overweight/obesity (BMI ≥ 25 kg/m 2 ) were only shown in rural areas, and those of high BP (SBP ≥ 120 mmHg or DBP ≥ 80 mmHg) were presented in low-income families and in regions of all modernization levels.…”
Section: Discussionmentioning
confidence: 99%
“…1-3 Growing evidence that dietary habits developed during childhood often persist into adulthood both raises concern and creates opportunity for intervention because poor dietary quality is recognized as a risk factor for chronic diseases among adults including diabetes, cardiovascular disease, and cancer. 4,5 However, we know relatively little about differences in the dietary quality of children at different ages in the developed world. Several indices exist to measure dietary quality and, although small differences exist, all focus on adherence to a diet that emphasizes vegetables, fruits, whole grains, low-fat dairy, fish, and unsaturated fatty acids.…”
Section: Introductionmentioning
confidence: 99%
“…Brown and Roberts [24] found that, among adolescents, timeconstant factors (i.e., genetics, individual characteristics, home environments) and time-changing factors (i.e., social network influences) explained 43 % and 44 %, respectively, of weight correlations across statistical models. Among adult-sibling models, the contribution of time-constant factors remained relatively high (33-38 %), but time-changing factors explained less variation (5-15 %).…”
Section: Correlates Of Obesitymentioning
confidence: 99%